MEDIA SUSTAINABILITY INDEX IN IRAQ - Al-Uqaili, Gehad Khazem (ALBAHITH ALALAMI, 2007)
The importance of this research lies in assessing the current state of media in Iraq based on international indicators and standards set by the Research and Scientific Exchange Council and UNESCO. That is to measure the strength and durability of media after 9 April 2003. These indicators are divided into five objectives that measure and describe each of the five research objectives that we seek to test through the points system. Based on the foregoing, researchers in Iraqi media find that these conditions may lead to further decline unless measures are taken to help avoid mistakes, provide the requirements for development and progress. In addition, care from the State is needed to support this process, which wouldn’t be rewarding and beneficial unless the State also requires:- Issuance of new legislation, that carries out the necessary conditions for the growth of a free and democratic press.- Emphasizes protection of journalists and promotes their active role in society.We hope through this research to setup development field studies in the formulation of a new thought on Iraqi media that address the imbalances of the position of the tribe, partisan intolerance, control of politicians and money in this important process. In addition to seek new formulas in the development of technical staff in editing and directing Management of marketing operations, field follow-up, conduct research, theoretical and field studies that will follow and diagnose the factors that help to encircle the manifestations of underdevelopment.